Factors Influencing the Efficiency of Solar Energy Systems - Eze, Val Hyginus Udoka; Richard, Kiiza; John Ukagwu, Kelechi; Okafor, Wisdom (Journal of Engineering, Technology, and Applied Science (JETAS), 2024)
The efficiency of solar panels is significantly influenced by temperature and irradiance, which are crucial in solar energy conversion. As temperatures rise, solar panel efficiency typically decreases due to increased electrical resistance, resulting in lower output voltage and power production. This efficiency loss is quantified by the temperature coefficient, indicating the drop per degree Celsius above 25°C. Advanced cooling systems and optimal thermal management can mitigate these effects. Irradiance, the sunlight intensity reaching the panels, directly affects electricity generation. While higher irradiance increases efficiency by providing more photons for conversion, it can also raise temperatures, negatively impacting performance. Solar panels achieve maximum efficiency under optimal irradiance and moderate temperatures, typically 1000 W/m² at 25°C. Variations in irradiance due to geographical location, time of day, and weather conditions cause fluctuations in power output. Efficient system design must consider local irradiance patterns and utilize tracking systems to maintain optimal panel orientation. To optimize efficiency, innovative methods such as advanced materials, cooling techniques, and smart tracking systems are employed. Additionally, integrating energy storage solutions and predictive analytics helps manage environmental impacts. Proper design, installation, and maintenance strategies are crucial for maximizing solar panel efficiency and lifespan under varying conditions. Understanding the interplay between temperature and irradiance is essential for advancing solar energy technologies, and enhancing their reliability and effectiveness in diverse environments.